In Vitro Cytotoxic Potential of Different Extracts of Cyclea peltata in HepG2 Cell Lines - Poonghuzhali, R.; Shankar, R.; Sujith, S.; Nisha, A. R.; Nair, Suresh N.; Priya, M. N. (International Journal of Bio-resource and Stress Management, 2025)
This experiment was conducted during March-April, 2022 in the Department of Veterinary Pharmacology and Toxicology, College of Veterinary and Animal Sciences, Mannuthy, Thrissur, Kerala, India to find out the cytotoxic potential of the different extracts and fractions of Cyclea peltata using MTT assay and AO/EB & JC-1 vital dye staining in HepG2 cell lines. Cyclea peltata also known as Padal belonging to the family Menispermaceae, was a slender twining climbing shrub, used largely for its antipyretic, diuretic, antioxidant, anti-inflammatory, anti-cancer and snake venom neutralising properties. The whole plant of C. peltata was collected from Thrissur, Kerala, was identified, dried and extracted using water and methanol and the methanolic extract was fractionated using n-hexane, dichloromethane, n-butanol and water. The cytotoxic potential was analysed using 3-(4, 5-dimethyl thazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay in HepG2 cell lines and its apoptotic nature was evaluated using acridine orange/ethidium bromide (AO/EB) and 5, 5’, 6, 6’ -tetrachloro-1, 1’, 3, 3’-tetra-ethyl benzimidazol-carbocyanine iodide (JC-1) staining. The extracts and fractions showed a dose dependent decrease in the viability of the cells exposed to it. The plant extracts of C. peltata especially n-hexane fraction was indicating a vital cytotoxicity in HepG2 cell lines through intrinsic pathway of apoptotic cell death and may be further analysed for the presence of detailed bioactive anti-cancer compounds and its potency.